My life as a meme - Tashjian, Janet (Tashjian, Janet. My life series., 2019)
Derek and his friends are dog-sitting Poufy, an Instagram-famous Shih Tzu, at her owner's mansion, where they lounge by the pool and help with Poufy's grooming and social media routine. When wildfires threaten the mansion, the group (and Poufy) are forced to evacuate to a local high school. A photo of Derek with Poufy on his lap goes viral and Derek has to deal with the social fallout.